Factors influencing tourist’s satisfaction, loyalty and word of mouth in selection of local foods in Pakistan - Muhammad, Ali; Puah, Chin Hong; Norazirah, Ayob; Syed Ali, Raza (Emerald Publishing Limited, 2019)
Purpose – Local foods from the perspective of tourism play a significant role to attract tourists. Surprisingly, empirical evidence on food tourism is quite scarce. The purpose of this paper is to develop and investigate a conceptual framework on tourist satisfaction, loyalty and word of mouth (WOM) to select local foods in Pakistan. Design/methodology/approach – The study uses a quantitative approach while convenience (non-probability) sampling is used to collect a sample of 286 final responses using a survey-based questionnaire. The study employed exploratory factor analysis and confirmatory factor analysis to stabilize the factor structure. The conceptual model is then tested under the assumptions of structural equation modeling. Findings – The findings indicate that food quality, perceived environmental quality, perceived value and service quality has a significant impact on the tourist’s satisfaction. However, interpersonal interaction quality shows an insignificant influence on satisfaction. Moreover, satisfaction has a significant impact on loyalty while loyalty further shows a significant effect on tourist WOM. Overall, the authors found satisfaction and loyalty are the major contributors to the hypothesized model. Practical implications – The conceptual framework and study findings will support practitioners and researchers to understand the factors that influence a tourist’s selection of local foods. Additionally, the study provides a useful policy to gain long-term economic benefits for the tourism sector in Pakistan. Originality/value – To the authors’ best knowledge, this study is the first attempt to explore WOM behavior in tourism research focusing on the critical role of satisfaction and loyalty. The authors are certain that the findings will contribute significantly to the existing body of knowledge.